Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
x = 16/7, y = -6/7
For elimination I will multiply the first equation by -3 to get the x to cancel
x - 2y = 4 --> -3x + 6y = -12
Now we bring back the other equation and treat it like an addition problem:
-3x + 6y = -12
3x + y = 6
+———————
7y = -6
y = -6/7
To get x we will use this y-value and plug it into one of the equations:
3x + y = 6,
3x + (-6/7) = 6
3x - 6/7 = 6
3x = 48/7
x = 16/7
So the solution is x = 16/7, y = -6/7, and if you are ever unsure you can put both of these values into both system of equations to see if the equations are true.
For elimination I will multiply the first equation by -3 to get the x to cancel
x - 2y = 4 --> -3x + 6y = -12
Now we bring back the other equation and treat it like an addition problem:
-3x + 6y = -12
3x + y = 6
+———————
7y = -6
y = -6/7
To get x we will use this y-value and plug it into one of the equations:
3x + y = 6,
3x + (-6/7) = 6
3x - 6/7 = 6
3x = 48/7
x = 16/7
So the solution is x = 16/7, y = -6/7, and if you are ever unsure you can put both of these values into both system of equations to see if the equations are true.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.